A functional component framework for integration infrastructures. (14th October 2004) - Van Busschbach, Erik; Pieterse, Bram; Zwegers, Arian
Enterprises cooperate extensively with other enterprises in various forms. These collaboration forms need suitable infrastructures and supporting applications to realise the collaboration. This paper presents ideas and requirements for an integration infrastructure and introduces a functional component framework that supports the development of an integration infrastructure. The evolution of enterprise business systems is accompanied by an evolution in the integration domain. The former results in current collaborative applications. The various technology and functionality features that an integration infrastructure should offer to enterprises to engage in c-commerce activities are described. An integration infrastructure capability stack is defined that contains a dimension consisting of connectivity, transformation, routing, and process management layers, and a dimension of functional environments.